in vitro Antidiabetic and Antimicrobial Activity of Methanolic Bark Extract of Cinnamomum obtusifolium (Roxb.) Nees - Sharma, Hemanta Kumar; Gogoi, Barnali (Asian Journal of Chemistry, 2016)
The present study was aimed to investigate in vitro antidiabetic and antimicrobial activity of methanolic bark extract of Cinnamomum obtusifolium. The a-amylase and a-glucosidase activities were measured in the presence of methanolic bark extract of Cinnamomum obtusifolium and acarbose, respectively. Antimicrobial activity was tested against six pathogenic bacterial strains and one fungal strain by agar well diffusion method. The results showed that methanolic bark extract of Cinnamomum obtusifolium had a-amylase and a-glucosidase inhibitory activity with half-maximal inhibitory concentration values of 31.26 and 170.135 μg/mL, respectively. The extract was found to exert low to moderate antimicrobial activity compared to a standard antimicrobial agent.